Islamic Story-Based Aqidah Akhlak Learning and ‎Moral-Value Manifestations: A Qualitative Case ‎Study in a State Islamic Elementary School - Khanifah Gesi Riskina; Saidah Ahmad; Andi Nurhasanah (Yayasan Darusssalam Bengkulu, 2026)
This study aimed to describe the implementation of Islamic story-based Aqidah Akhlak learning in instilling moral values among fourth-grade students at MIN Kota Jambi, identify supporting and inhibiting factors, and examine teachers’ efforts to improve its implementation. This qualitative case study examined Islamic storytelling in Aqidah Akhlak, a subject integrating Islamic belief (aqidah) and moral conduct (akhlak), in one fourth-grade class at a state Islamic elementary school (Madrasah Ibtidaiyah Negeri) in Jambi City. Participants were the head of the madrasah, one Aqidah Akhlak teacher, and 29 students (16 boys and 13 girls). Data were collected through direct classroom observation involving the focal class, semi-structured interviews with the head, teacher, and selected students, and analysis of lesson plans and relevant school documents. Data were coded, categorized, and refined into themes through iterative comparison and triangulation. Storytelling involved purposeful story selection, expressive narration, guided reflection, and observation of classroom conduct. The data showed observed or reported manifestations associated with religiosity, honesty, discipline, responsibility, politeness, and social care; these patterns do not establish causal behavioral change. Teacher competence, student engagement, leadership support, and religious routines supported implementation, whereas limited time, heterogeneous responses, and limited media constrained it. The study provides a context-specific account of how identification, reflection, modeling, and habituation were combined in Aqidah Akhlak learning.